(untitled) (Revista Tópos, 2013)
O arquiteto francês Christian de Portzamparc, ao refletir sobre o desenvolvimento urbano pautado quase que exclusivamente num modelo capitalista de produção do espaço, concebe um urbanismo por ele denominado de urbanismo da “3ª Era da cidade”. A concepção urbanista típica do medievo é compacta, fechada como uma concentração defensiva, aqui caracterizada como 1ª Era da cidade. O urbanismo da cidade moderna, da 2ª Era da cidade, pauta-se na busca pela comunicação entre a industrialização, a economia e o design. É a racionalização do viver, um urbanismo objetivado como uma máquina. Por sua vez, o urbanismo da “3ª Era da cidade” seria a síntese dialética entre o urbanismo medieval e o moderno, objetivando as quadras abertas como simbiose entre usos privados e públicos do espaço urbano. Palavras-chave: Urbanismo; Esfera Pública e Privada; Quadra Aberta. 3rd ERA OF THE CITY IN CHRISTIAN OF PORTZAMPARC: MORE THAN THE SAME THING? Abstract While thinking about the urbane development ruled almost exclusively in a capitalist model of production of the space, the french architect Christian de Portzamparc conceives a town planning for him called of town planning of the “3rd Era of the city”. The conception typical town planner of the medieval period is compact, closed like a defensive concentration, here characterized like 1st Era of the city. The town planning of the modern city, of the 2nd Era of the city, is ruled in the search by the communication between the industrialization, the economy and the design. It is the rationalization of living, a town planning aimed like a machine. For his time, the town planning of the “3rd Era of the city” would be the dialectic synthesis between the medieval town planning and the modern thing if it aimed at the blocks opened like symbiosis between private and public uses of the urbane space. Keywords: Town planning; Public and Private Sphere; Open Block.